2020
DOI: 10.1186/s12885-020-07340-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-based longitudinal mutation monitoring as a potential predictor of disease progression in subjects with adenocarcinoma in advanced non-small cell lung cancer

Abstract: Background Identifying and tracking somatic mutations in cell-free DNA (cfDNA) by next-generation sequencing (NGS) has the potential to transform the clinical management of subjects with advanced non-small cell lung cancer (NSCLC). Methods Baseline tumor tissue (n = 47) and longitudinal plasma (n = 445) were collected from 71 NSCLC subjects treated with chemotherapy. cfDNA was enriched using a targeted-capture NGS kit containing 197 genes. Clinical responses to treatment were determined using RECIST v1.1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Targeting multiple mutations simultaneously also elevates the sensitivity of detecting ctDNA [12,46]. Indeed, the number of ctDNA negative patients when using NGS approaches is substantially lower (4-8%) than was observed with our single variant assay [14,47]. Studies that used an NGS approach to monitor ctDNA in response to ICI therapy demonstrate a correlation between ctDNA dynamics and response similar to our findings [12,13,48].…”
Section: Accepted Articlesupporting
confidence: 81%
“…Targeting multiple mutations simultaneously also elevates the sensitivity of detecting ctDNA [12,46]. Indeed, the number of ctDNA negative patients when using NGS approaches is substantially lower (4-8%) than was observed with our single variant assay [14,47]. Studies that used an NGS approach to monitor ctDNA in response to ICI therapy demonstrate a correlation between ctDNA dynamics and response similar to our findings [12,13,48].…”
Section: Accepted Articlesupporting
confidence: 81%
“…More effective targeting of DTP populations may be a new strategy to delay or prevent acquired resistance from occurring 201 . Early intervention may also be facilitated by monitoring molecular tumour progression routinely and non-invasively using ctDNA from patient plasma samples, enabling earlier and more informed changes in treatment management to be deployed on the basis of molecular signals before clinical progression 202 , 203 . Opportunities in this area will expand significantly, as non-invasive technologies for detecting biomarkers become more sensitive and more widely available.…”
Section: The Next 20 Years Of Kinase Drug Discoverymentioning
confidence: 99%
“…For example, the detection of ctDNA in peripheral blood has shown great potential in the clinic, particularly for those patients who cannot undergo biopsy ( 52 54 ). Recent research found that in patients with advanced non-small cell lung cancer, elevation of ctDNA preceded an abnormal radiographic finding and the frequency of mutated alleles in ctDNA increased consecutively for 3-5 months before clinical evidence of disease progression ( 55 ). Moreover, as for melanoma patients, an undetectable ctDNA at baseline or during treatment tended to correlate with a better objective response to therapy ( 56 ).…”
Section: Discussionmentioning
confidence: 99%